The Effect of a Combination of Ultrasound and Stretching on the Pain Scores of Piriformis Syndrome Patients at the Padas Health Center, Ngawi Regency - Imani, Kelvin Teguh; Fariz, Achmad; Hamidah, Nurul (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Piriformis Syndrome is a pain in the pelvic area caused by prolonged or excessive contraction of the piriformis muscle so that the sciatic nerve is compressed or compressed. The physiotherapy treatment used is a combination of ultrasound and stretching. This study aimed to determine the effect of a combination of ultrasound and stretching in reducing pain in piriformis syndrome patients. Subjects and Method: The design of this study was a one-group pre-experimental and post-test design with 20 respondents who met the inclusion and exclusion criteria using a purposive sampling technique carried out in September-October 2023. Respondents had their pain scale measured using VAS (Visual Analog Scale) before and after physiotherapy treatment, namely; giving a combination of ultrasound and stretching 2 times a week for 4 weeks. Results: This study used the paired sample test hypothesis test with the median VAS value; (1) pre by 5.70; (2) posts by 3.35 and (3) P value by 0.00. Conclusion: It can be concluded that the combination of ultrasound and stretching is effective in reducing pain in cases of piriformis syndrome.